UDP-Glucuronosyltransferase-mediated Metabolic Activation of the Tobacco Carcinogen 2-Amino-9H-pyrido[2,3-b]indole - Tang, Yijin (American Society for Biochemistry and Molecular Biology, 2012)
2-Amino-9H-pyrido[2,3-b]indole (AαC) is a carcinogenic heterocyclic aromatic amine (HAA) that arises in tobacco smoke. UDP-glucuronosyltransferases (UGTs) are important enzymes that detoxicate many procarcinogens, including HAAs. UGTs compete with P450 enzymes, which bioactivate HAAs by N-hydroxylation of the exocyclic amine group; the resultant N-hydroxy-HAA metabolites form covalent adducts with DNA. We have characterized the UGT-catalyzed metabolic products of AαC and the genotoxic metabolite 2-hydroxyamino-9H-pyrido[2,3-b]indole (HONH-AαC) formed with human liver microsomes, recombinant human UGT isoforms, and human hepatocytes. The structures of the metabolites were elucidated by (1)H NMR and mass spectrometry. AαC and HONH-AαC underwent glucuronidation by UGTs to form, respectively, N(2)-(β-d-glucosidurony1)-2-amino-9H-pyrido[2,3-b]indole (AαC-N(2)-Gl) and N(2)-(β-d-glucosidurony1)-2-hydroxyamino-9H-pyrido[2,3-b]indole (AαC-HON(2)-Gl). HONH-AαC also underwent glucuronidation to form a novel O-linked glucuronide conjugate, O-(β-d-glucosidurony1)-2-hydroxyamino-9H-pyrido[2,3-b]indole (AαC-HN(2)-O-Gl). AαC-HN(2)-O-Gl is a biologically reactive metabolite and binds to calf thymus DNA (pH 5.0 or 7.0) to form the N-(deoxyguanosin-8-yl)-AαC adduct at 20–50-fold higher levels than the adduct levels formed with HONH-AαC. Major UGT isoforms were examined for their capacity to metabolize AαC and HONH-AαC. UGT1A4 was the most catalytically efficient enzyme (V(max)/K(m)) at forming AαC-N(2)-Gl (0.67 μl·min(−1)·mg of protein(−1)), and UGT1A9 was most catalytically efficient at forming AαC-HN-O-Gl (77.1 μl·min(−1)·mg of protein(−1)), whereas UGT1A1 was most efficient at forming AαC-HON(2)-Gl (5.0 μl·min(−1)·mg of protein(−1)). Human hepatocytes produced AαC-N(2)-Gl and AαC-HN(2)-O-Gl in abundant quantities, but AαC-HON(2)-Gl was a minor product. Thus, UGTs, usually important enzymes in the detoxication of many procarcinogens, serve as a mechanism of bioactivation of HONH-AαC.